2014
DOI: 10.1002/14651858.cd010191.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital versus in-hospital thrombolysis for ST-elevation myocardial infarction

Abstract: Pre-hospital versus in-hospital thrombolysis for ST-elevation myocardial infarction (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 81 publications
0
17
0
3
Order By: Relevance
“…Although primary PCI is the gold standard, guideline recommended treatment for STEMI, we suggest that patients could undergo fibrinolysis if the anticipated time from FMC to balloon inflation is greater than 90 min . In these patients, PHT effectively reduces time to treatment and total ischaemic time, based on studies conducted in higher income countries . In settings where it can be safely and correctly administered by trained staff and primary PCI is not timely available, PHT is an appropriate and evidence‐based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary PCI is the gold standard, guideline recommended treatment for STEMI, we suggest that patients could undergo fibrinolysis if the anticipated time from FMC to balloon inflation is greater than 90 min . In these patients, PHT effectively reduces time to treatment and total ischaemic time, based on studies conducted in higher income countries . In settings where it can be safely and correctly administered by trained staff and primary PCI is not timely available, PHT is an appropriate and evidence‐based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Library also demonstrates the limited utility of the evidence to inform practice. A review of the use of aminophylline for cardiac arrest found five trials with no survivors 3 . A report on prehospital thrombolysis showed a reduction in time to thrombolysis, but limited evidence of its safety or on its long‐term outcomes 4 .…”
Section: Relating Evidence To Practice In Uncontrolled Environmentsmentioning
confidence: 99%
“…In some studies, prehospital administration of thrombolytics for myocardial infarction (MI) has been shown to improve survival [14]. Unfortunately, this is not a common practice in the United States.…”
Section: Als Interventions and Survivalmentioning
confidence: 99%